Inclusion or outcomes?: tensions in the involvement of people with learning disabilities in strategic planning - Fyson, Rachel; Fox, Liz (Taylor & Francis, 2014)
Social inclusion is a key principle which underpins the provision of services for people with learning disabilities in England. Learning Disability Partnership Boards, which are responsible for local strategic planning of learning disability services, hold a particular role in promoting inclusion since they are required both to operate inclusively and to achieve inclusive outcomes. This study sought to explore the extent to which these ambitions for inclusion were being achieved. It consisted of three phases: a scoping exercise to elicit the views of key stakeholders; a postal survey of Partnership Boards (response rate 51%); and semi-structured interviews with Partnership Boards members in six local authorities. Findings suggest that Partnership Boards are struggling to fulfil their dual role, with tensions emerging between the desire to operate in fully inclusive ways and the ability to affect strategic change within local services.